PENGARUH PENGENDALIAN INTERN PENJUALAN KREDIT TERHADAP PIUTANG TAK TERTAGIH PADA PT. MULTI TOP INDONESIA CABANG TEBING TINGGI WILAYAH MEDAN PERIODE 2013 – 2017 - YENNY .; JEAN MORGAN HSIEH; REBECCA EVADINE SIAHAAN; DINA ROSMANELIANA (JURNAL ILMIAH SIMANTEK, 2018)
Receivables are claims of a company on the other side. Almost all entities have receivables from other parties both related tosales/income transactions and are receivables from other transactions. The purpose of this research is to know the impact ofthe internal control the sale of credit against receivables are not collected on PT Multi Top Indonesian branch The cliffs of thefield of the 2013-2017, both in partial and simultaneously. The samples used in this research is a monthly financial statementfor 5 years. The analysis are used in this research is through statistical analysis descriptive analysis and regression linearrisks. The research shows that a control of the internal credit sale significantly influences on debt not collected on PT MultiTop Indonesian branch The cliffs high for a periode of 2013-2017, with a percentage of 54 percent of the (the value of R2).